Visible-light-induced radical carbo-cyclization/gem-diborylation through triplet energy transfer between a gold catalyst and aryl iodides - Zhang, Lumin; Rominger, Frank; Hashmi, A. Stephen K. (Journal of the American Chemical Society, 2020)
Geminal diboronates have attracted significant attention because of their unique structures and reactivity. However, benzofuran-, indole-, and benzothiophene-based benzylic gem-diboronates, building blocks for biologically relevant compounds, are unknown. A promising protocol using visible light and aryl iodides for constructing valuable building blocks, including benzofuran-, indole-, and benzothiophene-based benzylic gem-diboronates, via radical carbo-cyclization/gem-diborylation of alkynes with a high functional group tolerance is presented. The utility of these gem-diboronates has been demonstrated by a 10 g scale conversion, by versatile transformations, by including the synthesis of approved drug scaffolds and two approved drugs, and even by polymer synthesis. The mechanistic investigation indicates that the merging of the dinuclear gold catalyst (photoexcitation by 315-400 nm UVA light) with Na2CO3 is directly responsible for photosensitization of aryl iodides (photoexcitation by 254 nm UV light) with blue LED light (410-490 nm, λmax = 465 nm) through an energy transfer (EnT) process, followed by homolytic cleavage of the C-I bond in the aryl iodide substrates.